2022
DOI: 10.3390/w14111697
|View full text |Cite
|
Sign up to set email alerts
|

Metrics Assessment and Streamflow Modeling under Changing Climate in a Data-Scarce Heterogeneous Region: A Case Study of the Kabul River Basin

Abstract: Due to many uncertainties in hydrological data and modeling, the findings are frequently regarded as unreliable, especially in heterogeneous catchments such as the Kabul River Basin (KRB). Besides, statistical methods to assess the performance of the models have also been called into doubt in several studies. We evaluated the performance of the Soil and Water Assessment Tool (SWAT) model by statistical indicators including the Kling-Gupta efficiency (KGE), Nash–Sutcliffe efficiency (NSE), and the coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Sohaib et al [42] found future seasonal shifts in the streamflow and the rainfall shifts at the Nowshera and Chitral watershed of KRB, and Ref. [18] found that the peak hydrograph split into two peaks; one formed in Mar-Apr indicated earlier snowmelt, and the second one in August, which was due to Monsoon rains increased in the Alingar watershed of the KRB. Our study suggests that the total runoff in the UKRB is expected to increase under RCP4.5 and RCP8.5, except for the 2090s in the RCP8.5 scenario.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sohaib et al [42] found future seasonal shifts in the streamflow and the rainfall shifts at the Nowshera and Chitral watershed of KRB, and Ref. [18] found that the peak hydrograph split into two peaks; one formed in Mar-Apr indicated earlier snowmelt, and the second one in August, which was due to Monsoon rains increased in the Alingar watershed of the KRB. Our study suggests that the total runoff in the UKRB is expected to increase under RCP4.5 and RCP8.5, except for the 2090s in the RCP8.5 scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ref. [18] conducted a study to assess the performance of SWAT, evaluate different statistical metrics during calibration and validation, and analyze the impacts of climate change on streamflow from 2020 to 2045 in the Alingar Watershed of the KRB. The results from Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation